Grifola Frondosa Polysaccharide (GFP) improves neutrophils immune function of heavy load exercising rats - Huang, Jian; Shi, Yali; Sun, Minjun (Progress in Nutrition, 2018)
Grifola frondosa polysaccharide (GFP) is the extract of Grifola frondosa. In this study, 50 male wistar rats were separated into S + C, S + T, LG + T, MG + T and HG + T groups to study the effect of GFP on the immune function of heavy load exercising rats. In S + T group, blood neutrophil number, neutrophil phagocytic index and bactericidal capacity decreased significantly, and adhesion function showed remarkable increase after 8 weeks excessive exercise. Low, medium and high doses of GFP were administered to different groups based on gavage. After gavaging GFP during the eight weeks of excessive exercise, blood neutrophils in the MG + T group and HG + T group were 15.3% and 7.9% higher than in the S + T group. The blood neutrophil phagocytic indices in the MG + T and HG + T groups increased to 1.19 and 1.20, respectively, from 1.02 in the S + T group. The neutrophil bactericidal ability of blood cells in the MG + T and HG + T groups was also observed to be 46.6% and 45.6%, respectively, in comparison with 39.7% for S + T and 39.2% for LG + T group. Blood neutrophil adhesion function in the MG + T and HG + T groups was 57.4% and 57.6%, respectively. This is significantly lower than 65.6% in the S+T group. We demonstrate that feeding a medium or high dose of GFP can improve the neutrophil immune function of excessively exercising rats. A medium dose of GFP shows the most significant effect.